Competências essenciais requeridas para o gerenciamento das linhas de produção da indústria alimentícia: a visão dos seus gestores - Carletto, Balduir (2006)
The present study aimed to identify the essential competences, required to production managers of large food industries in the Campos Gerais area, in their managers’ perspectives. The study was conducted under the vision of nature was applied, on the perspective of the quality approach, of the goals as exploratory, and under the perspective of the technical procedures as a case study and developed with four of the largest food industries in this area. The target public was formed by the Industry manager, production manager, and HR manager of these organizations, in a total of 11 managers, and for the data collecting the semi-structured recorded interview. After the organizing of the data, 13 essential competences were identified, as required to the production manager: analysis and solution of problems, technical competence, organizational compromise, compromise with quality, initiative, motivation, organization, responsibility, team work, capacity of maintaining good inter-personal relations, capacity to evaluate the production line, pro-activity, and capacity of negotiation. The identification, development, recognizing and evaluation of the competences make up an important change of paradigm, in relation to concepts and values, which will have great influence in the destiny of the organization, in the careers and in the evolution of society.